Tafsir Sufistik dalam Tradisi Penafsiran Al-Qur’an (Sejarah Perkembangan dan Konstruksi Hermeneutis) - Asep Nahrul Musadad (Farabi, 2015)
This article discusses one of interpretation styles of the Koran that is quite unique, the Sufi interpretation. As one of the traditions that become an integral part of the history of Islamic civilization, tasawwuf atausufisme, which widely became popular in the Islamic community in the 4th century AH / 10 AD, in turn, are also in contact with the Koran as the main source text in Islam from which is born of a chain of civilization. In particular, this paper will briefly review some of the major themes of the Sufi interpretation, including Sufism contact with the Koran, the early appearance of Sufi interpretation, development, and several major hermeneutical constructions that underlie the Sufi style interpretation.